The role of C-reactive protein in predicting all-cause mortality among Chinese arthritis patients: implications for public health education and promotion - Shuchao Ye; Damei Ye; Changyi Lin; Dongming Lu; Xuelan You; Chaoyan Xu; Yongyang Wu (Frontiers in Public Health)
ObjectiveArthritis poses a significant public health challenge, contributing to increased healthcare resource utilization and reduced quality of life. C-reactive protein (CRP), a key inflammatory biomarker, plays a critical role in monitoring disease progression and guiding health promotion strategies. This study aims to investigate the association between CRP levels and all-cause mortality in Chinese arthritis patients, highlighting its implications for public health education and intervention programs.MethodsA prospective cohort study was conducted using data from the China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2020. Individuals diagnosed with arthritis in 2011 were included, with CRP levels as the primary exposure variable and mortality as the outcome of interest. Kaplan–Meier survival curves and Cox proportional hazards regression models were employed to assess the relationship between CRP levels and mortality risk, emphasizing the potential for targeted health education and promotion interventions.ResultsA total of 3,413 participants were analyzed, with 87 deaths recorded during the 10-year follow-up period. Deceased individuals were older and exhibited higher levels of CRP, creatinine, and uric acid, alongside lower BMI, MET, eGFR, and HGB. Across three Cox regression models, elevated CRP levels (≥3 mg/L) were significantly associated with increased mortality risk [hazard ratio (HR) = 3.73 (2.23–6.23), HR = 3.00 (1.79–5.01), HR = 4.94 (1.77–13.78), respectively]. Kaplan–Meier survival curves further confirmed that arthritis patients with CRP levels ≥3 mg/L faced a markedly higher mortality risk.ConclusionElevated CRP levels are strongly associated with increased all-cause mortality in arthritis patients, underscoring the importance of integrating CRP monitoring into public health education and promotion strategies. Efforts to control inflammation and promote health literacy regarding arthritis management may improve survival outcomes and reduce the public health burden associated with arthritis.